Central Asia as a part of the Russian Empire - Morrison, Alexander Stephen (My University, 2011)
An excessively lengthy review article analysing the collectively-authored volume 'Tsentral'naya Aziya v Sostave Rossiiskoi Imperii', published by 'Novoe Literaturnoe Obozrenie' in 2007
'Центральная Азия в составе Российской Империи'
Keywords: Central Asian Studies; Central Asia (History)